A Review of Resveratrol as a Potent Chemoprotective and Synergistic Agent in Cancer Chemotherapy - Xiao, Qicai; Zhu, Wangshu; Feng, Wei; Lee, Su Seong; Leung, Albert Wingnang; Shen, Jun; Gao, Liqian; Xu, Chuanshan (Frontiers in Pharmacology, 2019)
Background: Cancer has become a major disease endangering human health around the world. Conventional chemotherapy suffers from many side effects including pain, cardiotoxicity, hepatotoxicity and renal toxicity. This review aims to describe a natural product of resveratrol as a chemoprotective and synergistic agent in the modulation of cancer chemotherapy. Methods: The publications were identified by comprehensive searching of SciFinder, PubMed, Web of Science, and our own reference library. Search terms included combinations of “resveratrol”, “cancer”, “natural products”, “chemotherapy”, and “side effects”. Selection of material focused on resveratrol reducing the side effects on cancer chemotherapy. Results: 31 references were referred in this review to outline resveratrol as a potent chemoprotective and synergistic agent in cancer chemotherapy, including 22 papers for describing the chemoprotective effects, and 9 papers for illustrating the synergistic effects. Conclusion: This study provides a systematic summary of resveratrol serving as a potent chemoprotective and synergistic agent to reduce the associated-side effects and enhance the therapeutic outcomes in cancer chemotherapy. Further studies in terms of resveratrol on a large amount of preclinical tests and clinical trials are highly demanded.